The Impact of Digital Economics on Economic Growth in Indonesia - Khodijah; Mardiah Kamila; Muhammad Rizki Siddiq (SMART Insight, 2022)
The purpose of this research is to determine the impact of the digital economy on economic growth in Indonesia. The research method uses a quantitative model to measure the role and influence of the digital economy on economic growth, using a regression analysis model. The data used are secondary data sourced from BPS, BI, internet search, and other related sources. Based on the results of the research, it shows that the digital economy has business resilience and is significantly able to make a positive contribution to economic growth. The conclusions of this study show that the digital economy is an economic sector that will continue to grow rapidly in the future. There is a need for the availability of a complete digital economy database that can be accessed by researchers, so that they can contribute ideas, in turn the digital economy is able to play a role as business resilience and make a positive contribution to sustainable economic growth.